John Nash: Three Phases in the Career of a Beautiful Mind - Capps, Donald (Journal of religion and health, 2005)
This article is the Helen Flanders Dunbar Lecture presented at Columbia-Presbyterian Hospital in New York City in 2002, the centennial year of her birth. It focuses on three periods in the evolution of Nash's mental illness, the predelusional, delusional, and postdelusional periods, and provides a psychoanalytic interpretation of each.